INVESTIGATING PATHOMORPHOLOGICAL CHARACTERISTICS OF THE UMBILICAL CORD IN CLINICAL MODELS OF PREECLAMPSIA - Rakhmanova N.Kh.; Kattakhodzhaeva M.Kh. (Western European Studies, 2024)
The world pays special attention to the diagnosis and treatment of hypertensive conditions in pregnant women, as well as related complications. Perinatal complications that occur after childbirth in women with preeclampsia and eclampsia are an urgent problem in modern medicine. To solve issues related to preserving the life and health of the mother and child, innovative approaches are needed in the study of all links of the mother-placenta-fetus system, including the use of clinical and pathomorphological methods
Keywords: preeclampsia; umbilical cord; eclampsia